Disturbance Observer Design for Controlling the Speed of Three Phase Induction Motor - Josaphat Pramudijanto; Fauzi Imadudin Adhim; Lucky Putri Rahayu; Muhamad Zulfiqar Rusretin (JAREE (Journal on Advanced Research in Electrical Engineering), 2018)
Induction Motor is a type of motor that is most widely used in industry compared to other electrical motors,  because this type of motor has several advantages such as construction simplicity, sturdiness, cheap prices and low maintenance need. But the main challenge is to keep the speed remain constant when the induction motor is given many various values of load until particular value of the load nominal is given, so the response of the motor will change varily even if a controller has been given, thus controlling the speed of three phase induction motor is much more difficult to do. Therefore, in this research, we applied Disturbance Observer (DOB) method using Proportional Integral Derivative (PID) controller. This method was chosen because it can automatically reduce or even eliminate the disturbance, which is in the form of load and the measurement noise. The use of PID controller was expected to enhance the motor’s time settling. The test result of the Disturbance Observer method shows that it can reduce the measurement noise in every loading scenario. While the simulation result shows that the response of PID controller + DOB are capable of approaching the nominal load response with a response specification of 0.1 % of plant error, overshoot or undershoot of 1.5 %, time settling (ts) 5 % by 7.1 seconds and time rises (tr) of 2.2 seconds. Keywords: Disturbance Observer, Proportional Integral Derivative, Induction Motor